The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2cp02929d
|View full text |Cite
|
Sign up to set email alerts
|

Medium dependent optical response in ultra-fine plasmonic nanoparticles

Abstract: We study the influence of media on the interaction of ultra-fine plasmonic nanoparticles ($\leq$8~nm) with radiation. The important role of the surface layer of the nanoparticles, with properties that differ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that there is spectral tuning with a change in the embedding medium, with air medium showing a peak in the UV region, SiN medium showing a peak in the visible region, and Si medium showing a peak in the infrared region. Sørensen et al 148 studied the effect of the medium on the optical response. It has been found that there is a direct correlation between the refractive index and the amplitude of the plasmon resonance.…”
Section: Integrating Additional Effectsmentioning
confidence: 99%
“…It has been shown that there is spectral tuning with a change in the embedding medium, with air medium showing a peak in the UV region, SiN medium showing a peak in the visible region, and Si medium showing a peak in the infrared region. Sørensen et al 148 studied the effect of the medium on the optical response. It has been found that there is a direct correlation between the refractive index and the amplitude of the plasmon resonance.…”
Section: Integrating Additional Effectsmentioning
confidence: 99%